Levels of lateral thinking among a sample of graduate students at the Tishreen University - Mansour, Ali; Diab , Rami (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
Find mainly aims to know the levels of lateral thinking among a sample of graduate students in the School of Education, University of October and you know the difference between the average scores of the research sample in lateral thinking individuals depending on variables: jurisdiction, the school year. The study sample consisted of 84 students from the MBA students at Tishreen University College of Education is the most important findings of the research: - The lateral thinking among graduate students is located in the low and middle levels similar percentage - There is a difference between the sample in lateral thinking individuals depending on the variable year - There is a difference between the sample in lateral thinking individuals depending on the variable Specialization The search is over to a set of proposals: 1. Know the level of lateral thinking among other categories. 2. educational curriculum development to keep pace with scientific developments. 3. practice teachers to be able to transfer lateral thinking to students at universities and schools skills. 4. Work on the introduction of the principles of lateral thinking in the curriculum. 5. to conduct a study to reveal the relationship of lateral thinking other types of thinking 6. study the relationship with some lateral thinking and cognitive psychological variables such as: Personal Styles Emotional intelligence 7. conduct a study to uncover the factors affecting the lateral thinking.